The prognostic value of four interleukin-1 gene polymorphisms in caucasian women with breast cancer – a multicenter study - Grimm, Christoph (BioMed Central, 2009)
BACKGROUND: The proinflammatory cytokine interleukin-1 (IL-1) is known to play an important role in the carcinogenesis of breast cancer. Although IL-1 gene polymorphisms were reported to be associated with increased risk of breast cancer, their influence on survival of Caucasian breast cancer patients remains to be shown. METHODS: We studied the influence of four common gene polymorphisms (IL1A -889C/T, IL1B -511C/T, IL1B +3953E1/E2, and IL1RN long/2) of the IL-1 family on survival in 262 Caucasian patients with breast cancer by univariate and multivariate survival analysis. The combined effect of the four gene polymorphisms on overall survival was studied by haplotype analysis. RESULTS: In the present study 38 cases of cancer related death and a median time of follow-up (range) of 55.3 (0.4–175.8) months was observed. IL1RN 2/2 (homozygous mutant) gene polymorphism was associated with shortened disease free and overall survival in a univariate (p = 0.001 and p = 0.01, respectively) and multivariate analysis (p = 0.002, Odds Ratio [95% Confidence Interval] = 3.6 [1.6–8.0] and p = 0.05, Odds Ratio = 3.0 [1.1–9.3], respectively). Presence of the homozygous mutant genotype of the IL1A -889 and IL1B +3953 gene polymorphism was associated with overall survival in the univariate (p = 0.004 and p = 0.002, respectively), but not in the multivariate analysis. No association was observed between all possible haplotype combinations and overall survival. CONCLUSION: Carriage of the mutant alleles of IL1RN was independently associated with shortened disease free and overall survival rates in Caucasian patients with breast cancer.